The relevance of self-compassion as an intervention target in mood and anxiety disorders: A narrative review based on an emotion regulation framework - Finlay-Jones, Amy (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 The Australian Psychological Society Background: There is growing interest in self-compassion as a possible treatment target for individuals with depression and anxiety disorders. Understanding self-compassion within an emotion regulation (ER) framework of mood and anxiety disorders has the potential to generate insights into the clinical relevance of self-compassion in the treatment of depression and anxiety. The aim of the current review was to integrate evidence and theory from the self-compassion, ER, and mood and anxiety disorders literatures to highlight directions for research and inform clinical applications. Methods: A review of the cross-sectional and experimental quantitative literature pertaining to self-compassion, ER, and mood and anxiety disorders was undertaken, guided by established models of ER in mood and anxiety disorders. Evidence from clinical and non-clinical studies was included. Results: There is preliminary support for an ER framework of self-compassion and mood and anxiety disorders: in particular, there is evidence that self-compassion is linked to factors that represent key mechanisms in ER models of depression and anxiety, including affective experiences, ER capacities, and propensity to deploy specific ER strategies. However, research with clinical populations is limited. Conclusions: An ER perspective may provide a useful framework for guiding research and clinical work on self-compassion and mood and anxiety disorders. Further research is required to comprehensively test the relationship between self-compassion and various aspects of the ER model, and to examine mediators and moderators of compassion-based interventions with clinical samples.